2013
DOI: 10.2340/16501977-1064
|View full text |Cite
|
Sign up to set email alerts
|

Evalution of Mulligan’s technique for adhesive capsulitis of the shoulder

Abstract: Mulligan's technique and passive stretching exercises are both effective in reducing pain, and restoring range of motion and function. However, compared with stretching exercises, Mulligan's technique led to better improvements in terms of pain, range of motion, shoulder scores, and patient and physiotherapist satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 17 publications
0
32
1
4
Order By: Relevance
“…A greater reduction in disability scores was seen in the MWM with exercise group, which supports the results of previous studies investigating posterolateral glide MWM for shoulder disability. 60,15,27 There are some limitations to this study's findings. Firstly, subjects were patients attending the Orthopaedic and Physiotherapy departments of a general hospital, with a specific limitation of HBB, hence results may not be generalized to all shoulder impairments and disorders.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A greater reduction in disability scores was seen in the MWM with exercise group, which supports the results of previous studies investigating posterolateral glide MWM for shoulder disability. 60,15,27 There are some limitations to this study's findings. Firstly, subjects were patients attending the Orthopaedic and Physiotherapy departments of a general hospital, with a specific limitation of HBB, hence results may not be generalized to all shoulder impairments and disorders.…”
Section: Discussionmentioning
confidence: 85%
“…26,42 In those studies a posterolateral glide MWM induced significantly greater improvement in shoulder flexion ROM when compared to placebo and control interventions which was sustained and further improved when used in conjunction with rigid sports tape applied to the skin to maintain the repositioning of the humeral head consistent with the MWM technique. Another study 27 found significant improvement in both active and passive ROM of all shoulder movements following a treatment program incorporating MWM applied in flexion, elevation and internal rotation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…75 In the low-quality trial comparing a specific PT technique with standardized PT alone, the specific technique (Mulligan's mobilization) was superior to passive stretching at 3 weeks and 3 months post-intervention. 71 In a high-quality trial comparing standardized PT with standardized PT plus intra-articular hyaluronic acid injection, both groups improved significantly but there was no added benefit to the injection. 72 In an acceptable-quality trial comparing SSNB injection before a course of PT with PT alone, both groups improved significantly immediately and 1 month post-intervention.…”
Section: Adhesive Capsulitismentioning
confidence: 99%
“…21 This questionnaire is mostly used in research and clinical practice in several countries, and its scores can range from 0 to 100, where 0 = no functional limitation and 100 = affirmative to all items; so the higher the scores, the higher the disability. 22,23 Other effect treatment outcomes were glenohumeral AROM (flexion, abduction, and external and internal rotations) measured with a universal goniometer (Enraf Nonius ibérica, Madrid, Spain) and pain intensity measured with the 11-point Verbal Numeric Rating Scale for its good reliability, validity, and usefulness in older adults. 24 For data collection, 4 physical therapy assessments were performed: at baseline (A0), immediately after group interventions (A1), after 1 month (A2), and after 3 months postintervention (A3).…”
Section: Measurement Of Clinical Outcomesmentioning
confidence: 99%